Letter writing as a reflective practice: understanding the shuffling, shifting, and shaping of a researcher identity. Issue 3 (4th May 2017) - Channa, Liaquat A.
Abstract: This article presents letter writing as a form of arts-based inquiry and reflective practice. The author argues that letter writing can be employed to develop a reflective space for autobiographical reflection. The letter featured here captures and demonstrates the shuffling, shifting, and shaping processes of the author's researcher identity through letter writing, and is informed by the theoretical underpinnings of reflective practice. It records and investigates the experiences that the author underwent during a compulsory course in the first year of a doctoral program at a North American university. Three interrelated themes are identified in the letter: the researcher identity in crisis, the nature of research, and future researcher identity. It is concluded that letter writing can facilitate the self-evolution, self-introspection, self-awareness, and identity change that emerges with, and through, reflection. Letter writing as a reflective practice offers the benefits of developing self-knowledge, independent thought, critical thinking, and deconstructive understanding of one's experiences.